(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
The research was carried out during the spring season of the 2021 season in the area (Wata Al-Bislis - Latakia) with the aim of testing the effectiveness of inoculation with bacterial fertilizers and the dates of their addition in some growth and productive indicators of potato plants. Use the Sponta potato variety for this. The research included thirteen treatments: control - untreated plants, and three bacterial fertilizers with four methods of adding each of them (addition at planting D1, the second after germination D2, the third at the beginning of ovulation D3, and the fourth included the three dates together D4). The research was carried out in a completely randomized block design, with three replicates for each treatment, with an average of 8 plants per replicate. The results of the study showed that the plants inoculated with the fertilizers used were significantly superior to the control plants. The study also showed that inoculation with the third bacterial fertilizer M3 (a mixture of the first two fertilisers, M1 and the second M2), and at the three times together, recorded the best results and the highest values ​​in the indicators studied, as the leaf surface area of ​​the plant and its index recorded a value of (13,300 cm2) and (4.70), respectively. It also recorded the best results were in the number of tubers and average tuber weight with a value of 7.43 tubers and 115.9 g/tuber, in plant production (861.1) g/plant, and productivity per unit area in g/m2, with a production efficiency of 45.9% compared to the control.